Omega‐3 fatty acids increase OXPHOS energy for immune therapy of Alzheimer disease patients. Issue 8 (2nd July 2020) - Lau, Yik Chai Charles; Ding, Jessica Aliyah; Simental, Aracely; Mirzoyan, Hayk; Lee, William; Diamante, Graciel; Cely, Ingrid; Tran, Michelle; Morselli, Marco; Dang, Johnny; Kaczor‐Urbanowicz, Karolina Elżbieta; Sayre, James; et al.
Abstract: Sporadic late‐onset Alzheimer disease (LOAD) preceded by mild cognitive impairment (MCI) is the most common type of dementia. Long‐term studies of immunity to pathogenic amyloid‐β (Aβ) in LOAD are lacking. Innate immunity of LOAD patients is malfunctioning in phagocytosis and degradation of Aβ and LOAD patients' macrophage transcriptome and metabolome are deregulated. We previously showed omega‐3 fatty acid (ω‐3)‐mediated repair of unfolded protein response and here we show much broader transcriptomic effects. ω‐3 treatment in vitro and ω‐3 supplementation by the drink Smartfish (SMF) in vivo increased the transcripts of the genes and pathways of immunity, glycolysis, tricarboxylic acid cycle, OX‐PHOS, nicotinamide dinucleotide (NAD + ) synthesis, and reversed the defects in Aβ phagocytosis. In both peripheral blood mononuclear cells (PBMC) and macrophages, ω‐3 increased ATP‐linked oxygen consumption rate (OCR) and ω‐3 with carnitine was superior to ω‐3. ω‐3 treatment in vitro and supplementation by the ω‐3 drink SMF in vivo rescued macrophage phagocytosis when glycolysis or glycosylation were blocked. ω‐3 provide flexible energy for immune clearance of the brain throughout the diurnal cycle, even in hypo‐ or hyper‐glycemia. In certain LOAD patients, ω‐3 may delay progression to dementia.